2014
DOI: 10.1128/ec.00330-13
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Posttranslational Regulation of the Gamete Fusogen GCS1 in the Isogamous Volvocine Alga Gonium pectorale

Abstract: f Male and female, generally defined based on differences in gamete size and motility, likely have multiple independent origins, appearing to have evolved from isogamous organisms in various eukaryotic lineages. Recent studies of the gamete fusogen GCS1/HAP2 indicate that this protein is deeply conserved across eukaryotes, and its exclusive and/or functional expression generally resides in males or in male homologues. However, little is known regarding the conserved or primitive molecular traits of males and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Several C. elegans genes are known to be essential for fertilization, but whether they function directly in the membrane fusion reaction is unknown because of the difficulty of experimentally defining distinct steps in gamete interactions (Singson et al, 2008). To date, the sole, broadly conserved protein shown by gene disruption to be essential for the gamete membrane fusion reaction in any system, including all model organisms, is the membrane protein HAP2 (also called GCS1), which is present in plants and protists, and in some multicellular animals (but notably absent in vertebrates) (Mori et al, 2006;von Besser et al, 2006;Liu et al, 2008Liu et al, , 2010Hirai et al, 2008;Goodman and McFadden, 2008;Cole et al, 2014;Steele and Dana, 2009;Ebchuqin et al, 2014;Kawai-Toyooka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Several C. elegans genes are known to be essential for fertilization, but whether they function directly in the membrane fusion reaction is unknown because of the difficulty of experimentally defining distinct steps in gamete interactions (Singson et al, 2008). To date, the sole, broadly conserved protein shown by gene disruption to be essential for the gamete membrane fusion reaction in any system, including all model organisms, is the membrane protein HAP2 (also called GCS1), which is present in plants and protists, and in some multicellular animals (but notably absent in vertebrates) (Mori et al, 2006;von Besser et al, 2006;Liu et al, 2008Liu et al, , 2010Hirai et al, 2008;Goodman and McFadden, 2008;Cole et al, 2014;Steele and Dana, 2009;Ebchuqin et al, 2014;Kawai-Toyooka et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the almost complete identity of the HAP2/GCS1-coding regions in the mt and mt + genomes, the regulatory system of this gene, which involves an alternative splicing mechanism, may have evolved specifically in this Ulva species. A post-translational GCS1/HAP2 regulatory system has been detected in the colonial volvocine Gonium (Kawai-Toyooka et al 2014). HAP2/GCS1 is regulated by generative cell-specific expression in land plants, and the protein is transported from the endomembrane system to the plasma membrane (Mori et al 2006, von Besser et al 2006, Asterisk indicates a significant difference between treatments by pairwise comparison of proportions without continuity (p 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, it was found that GCS1 is not angiosperm specific and that putative GCS1 orthologs are also present in algae, unicellular protists, amebae, and metazoans (Mori et al, 2006;Hirai et al, 2008;Liu et al, 2008;Steele and Dana, 2009;Kawai-Toyooka et al, 2014). Of such non-angiosperm species, gamete-specific expression of GCS1 was initially shown in the slime mold Physarum polycephalum and the green alga Chlamydomonas (Mori et al, 2006).…”
Section: Research History Of Gcs1 the Gamete Fusion Factor Conservedmentioning
confidence: 99%
“…Although the significance of the male dependent GCS1 function is still elusive, a recent GCS1 study using the green alga G. pectorale revealed a molecular system that gives rise to male dependence (Kawai-Toyooka et al, 2014). Specific antibodies against G. pectorale GCS1 (GpGCS1) showed that GpGCS1 in plus gametes is present at a substantial level before activation, besides minus gametes, suggesting that transcriptional regulation is not sufficient to restrict the GpGCS1 function to the minus sex.…”
Section: Research History Of Gcs1 the Gamete Fusion Factor Conservedmentioning
confidence: 99%
See 1 more Smart Citation